I feel at home: an analysis of the perception of Immigrant East African road runners in Brazil - Jeferson Roberto Rojo; Wycliffe Wekesa Simiyu Njororai; Giovana Xavier de Moura; Francielle Ferreira da Rocha; Fernando Augusto Starepravo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The present study aimed to analyze the perception of road runners of East African origin about the reception and hospitality extended to them by local athletes during the period in which they lived and competed in Brazil. A qualitative approach was used, appropriating sources acquired through interviews conducted by the authors of the study and documentary research. Among other findings, it was established that there was a distinction between personal relationships and the positioning of professional interests between Brazilian and East African athletes. In other words, as much as foreigners feel well received in Brazil, when they enter the professional part, Brazilian athletes express discontent with the presence of these foreign athletes in the country. The interview results and documentary analysis point to a contradiction. East African runners are considered athletic superstars and are admired by Brazilian runners. However, when it comes to professional relationships, Brazilians worry about financial losses related to race prizes when competing with top-performing African athletes.